O enquadramento das águas doces superficiais no Brasil: desafios e potencialidades para a gestão da qualidade hídrica - Faria, Pedro Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The superficial water bodies framing is an instrument of water management that consists in the classification of water bodies into quality classes, acording to the preponderant uses that are assigned to them. To have an effective application of the superficial water bodies framing, were created five water quality classes, being them Special, 1, 2, 3 and 4, in which the uses of the superficial waters are more noble in the classes of better quality. Therefore, the water bodies framing is a necessary measure for water conservation, for that reason, the purpose of this paper is to indentify the main dificulties and potentialities to implement this instrument in the management of brazilian watersheds. To obtain these data, a questionnaire was sent to the brazilian watersheds committes and for some water resources area researchers, five different basin plans were also analyzed, each reffering to an administrative region in the brazilian territory (South, Southeast, North, Northeast and Midwest). The main challenges found in the analisis of the basin plans and the answers to the questionnaire were the lack of water quality monitoring stations, the lack of technicians in the managing bodies, the lack of financial resources, the lack of studies that offers subsidy to the water bodies framing proposals, the water bodies pollution, the lack of data about the licensed enterprises, and the lack of institutional articulation between water managing bodies and the cities. This dificulties, when solved, represents the potentialities that the watersheds have to aprimorate the water management, because they are very important and relevant to the watersheds diagnosis and to the implementation of water bodies framing proposals.

O enquadramento das águas doces superficiais é um instrumento de gestão hídrica que consiste na classificação dos corpos hídricos em classes de qualidade, de acordo com os usos preponderantes que são atribuídos aos mesmos. Para que se tenha uma aplicação efetiva do enquadramento, foram criadas cinco classes de qualidade hídrica, sendo elas a classe Especial, 1, 2. 3 e 4, em que os usos das águas superficiais são mais nobres nas classes de melhor qualidade. Desta forma, o enquadramento é uma medida necessária para a conservação hídrica, logo, o objetivo do trabalho, é identificar as principais dificuldades e potencialidades de se implementar o instrumento nas bacias hidrográficas do Brasil. Para se obter estes dados, um questionário eletrônico foi enviado para os Comitês de Bacia brasileiros e para pesquisadores da área de recursos hídricos, também foram analisados cinco diferentes Planos de Bacia, cada um referente a uma região administrativa do território brasileiro (Sul, Sudeste, Norte, Nordeste e Centro-Oeste). As respostas e os Planos de Bacia foram analisados e os principais desafios encontrados foram a falta de postos de monitoramento da qualidade hídrica, a falta de técnicos nos órgãos gestores, a falta de recursos financeiros, a falta de estudos que ofereçam subsídio para as propostas de enquadramento, a poluição dos corpos hídricos, a falta de dados sobre empreendimentos licenciados e que possuam outorga e a falta de articulação institucional entre os órgãos gestores de recursos hídricos e os municípios. Estas dificuldades, quando solucionadas, representam as potencialidades que cada Bacia Hidrográfica possui para aprimorar a gestão hídrica de suas águas doces superficiais, pois são pontos de grande importância e relevância para o diagnóstico das bacias e para a implementação das propostas de enquadramento.
The superficial fresh water bodies framing in Brasil: difficulties and potentialities for water quality management
Keywords: Water resources; Water management; Water quality; Water bodies framing; Water bodies; Watersheds; Recursos hídricos; Qualidade hídrica; Enquadramento; Gestão hídrica; Bacia hidrográfica; Corpos hídricos